Impact of Various Pre-Treatments on the Lignocellulosic Compositions of Sarawak ‘Paun’ Pineapple Leaf Waste - Alexandra Cheryl, Dennis; Rosmawati, Saat; Diana Kertini, Monir (UNIMAS Publisher, 2025)
Pre-treatment of lignocellulosic biomass is a crucial step in breaking down the complex structure of the plant`s cell wall to enhance the availability and digestibility of cellulose for bioconversion process of the biomass to value-added products. The overall efficiency of the process designed to convert lignocelluloses also lies on an accurate determination of compositions of the lignocellulosic substrate. In this study, local species of Sarawak ‘Paun’ pineapple leaves collected from Simunjan, Sarawak, were subjected to various pre-treatment methods including thermal treatment, acidic treatments and alkaline treatments. Compositional analyses of the raw and pre-treated leaves were conducted through a gravimetric method to study the effect of different methods of pretreatments in altering the lignocellulosic compositions of the pineapple leaf wastes focusing on the hemicellulose, lignin and cellulose content. As the main purpose of a pre-treatment method focuses on its ability and efficiency to disintegrate the biomass complex structure, especially, in reducing lignin content for higher cellulose accessibility of enzymes in enzymatic hydrolyses. This study suggested that pretreatment with 1.5% (v/v) hydrochloric acid solution displayed the most notable change to the lignocellulose contents of the leaves as highest cellulose content (51.5% w/w) and lowest amount of lignin (10.3% w/w) were recorded, compared to that of other pre-treatment methods. These findings may provide a better understanding for future research in designing a suitable biochemical process with enhanced enzymatic digestibility of cellulose present in the pineapple leaves to yield wealth-added products.